Population structure of lamp shells (Brachiopoda: Lingula anatina Lamarck, 1801) in Aceh Northern Shore, Indonesia. Issue 1 (November 2021) - Octavina, C; Ulfah, M; Nurfadillah, N; Agustina, S; Niwatana, J; Al-Ihsan, M T; Irsyad, M
Abstract: This study aimed to determine the population structure of Lingula sp. in the Aceh northern shore. This research uses purposive sampling method where the sampling locations at Ujong Pancu beach, Kuala Cangkoi beach, Syiah Kuala beach and Alue Naga beach. Sampling was carried out using a quadratic transect (1x1 m) with three stations at each location. The results showed that there is one type of Brachiopods, namely the genus Lingula (Bruguière 1791), species Lingula anatina Lamarck, 1801 which are scattered on the north coast of Aceh. Overall, the abundance of L. anatina was quite high at each location, especially at Kuala Cangkoi beach (2.43 ind/m 2 ), while the lowest abundance was found at Ujong Pancu beach (1, 11 ind/m 2 ). In addition, it was also found that L. anatina had a similarity distribution on the Aceh northern shore. The existence of L. anatina on the Aceh northern shore is very dependent on good environmental conditions, in general, the quality of the waters of Aceh northern shore is still within the tolerance limits of these biota. Therefore, population structure of L. anatina is stable, so that this biota resource must continue to be considered and managed properly.